VD_FINDINFO HC / 2011 / 323 vom 7. Juni 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN | 176 CC, 179 CC, 308 al. 1 let. b CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH)